2012
DOI: 10.1615/jwomenminorscieneng.2012002908
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Achievement and Higher-Education Representation of Under-Represented Groups in Science, Technology, Engineering, and Mathematics Fields: A Review of Current K-12 Intervention Programs

Abstract: The under-representation of women and ethnic minorities in Science, Technology, Engineering, and Mathematics (STEM) education and professions has resulted in a loss of human capital for the US scientific workforce and spurred the development of myriad STEM educational intervention programs. Increased allocation of resources to such programs begs for a critical, prescriptive, evidence-based review that will enable researchers to develop optimal interventions and administrators to maximize investments. We begin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
80
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(85 citation statements)
references
References 61 publications
0
80
0
2
Order By: Relevance
“…Much of the literature related to the effectiveness of out of school time or informal pipeline programming suggests the need to start early to support girls in STEM: elementary or middle school (Hughes, 2015;Leaper, 2014;Heaverlo, Cooper, & Santos Lannan, 2013;Valla & Williams, 2012;VanLeuvan, 2004;Fadigan, & Hammrich, 2004;Clewell, 2002;Clewell & Campbell, 2002). Many of the factors that negatively influence women from choosing STEM majors and careers take shape early in a girl's life.…”
Section: Middle School As An Important Time For Interventionmentioning
confidence: 99%
“…Much of the literature related to the effectiveness of out of school time or informal pipeline programming suggests the need to start early to support girls in STEM: elementary or middle school (Hughes, 2015;Leaper, 2014;Heaverlo, Cooper, & Santos Lannan, 2013;Valla & Williams, 2012;VanLeuvan, 2004;Fadigan, & Hammrich, 2004;Clewell, 2002;Clewell & Campbell, 2002). Many of the factors that negatively influence women from choosing STEM majors and careers take shape early in a girl's life.…”
Section: Middle School As An Important Time For Interventionmentioning
confidence: 99%
“…Second, the TAR mentorship is integrated with a supporting STEM curriculum that also involves teachers as mentors. Findings from other STEM programs demonstrate the effectiveness of both long-term guidance and role models for high school students, especially females and underrepresented minorities 7,8 . The impact of the long-term TAR mentorship will be significant, and the program itself appealing especially to students often underrepresented in STEM programs, such as females, underrepresented ethnic minorities, the economically disadvantaged, and first-generation college aspirants; these students often do not engage with a STEM professional as an active role model.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from Dick's study showed that both men and women who chose to major in engineering relied on the advice of parents and teachers more than their peers, and family influences were particularly strong for the participants in our project 16,17 . Moreover, without early intervention and exposure, students can become disinterested in science and math, underestimate their abilities, and develop misconceptions about what type of person achieves a career in a STEM field 30 .…”
Section: Introductionmentioning
confidence: 99%
“…But one consensus among researchers regarding recruitment is to start early. Multiple studies have shown that early intervention is imperative as students begin to lose interest in math and science, limiting their career paths early in their education [31][32][33][34] . The National Academy of Engineering recommends successful engagement of students in STEM subjects in grammar school 35 .…”
Section: Introductionmentioning
confidence: 99%